STRUKTUR KOMUNITAS PERIFITON DIBAGIAN HULU SUNGAI CISADANE, KAWASAN TAMAN NASIONAL GUNUNG HALIMUN SALAK, JAWA BARAT - Pratiwi, Niken TM; Hariyadi, Sigid; Kiswari, Dhona Indah (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTPerifiton is one community of organisms that can adapt and thrive in the river, and relatively settled in one location. Riparian vegetation in the Mountain Halimun-Salak National Park could be expected to affect the community structure of periphyton. The purpose of this study was to identify the community structure of periphyton on different vegetation canopy coverage, to analyze relationship between the communities structure of periphyton and upstream Cisadane water quality conditions, and to determine water quality based on perifiton community. There were three sets three stations based on canopy coverage (80%, 60%, dan 40%). The results showed two groups of stations, the high canopy coverage (80%) and the low canopy coverage. The highest perifiton abundance was found at stations low canopy coverage, that dominated by Bacillarophycae, Pennales order, especially Navicula with higher rate of succesion than the higher canopy caverage. Abundance of periphyton of low canopy coverage was affected by ammonium, turbidity, and water current. Furthermore, in stations high canopy coverage it was influenced by orthophosphate and currents. As a whole, the periphyton community at upstream of Cisadane indicated a good condition of water quality.Keywords: canopy, periphyton, succession rate